The story of elimination of visceral leishmaniasis (kala-azar) in India-Challenges towards sustainment. - Shyam Sundar (PLoS Neglected Tropical Diseases)
The earliest record of visceral leishmaniasis (kala-azar, KA, VL) dates back two centuries from Jessore (now in Bangladesh), with 0.75 million deaths in 3 years. In the 1950s, there was extensive insecticide dichlorodiphenyltrichloroethane (DDT) spray under the aegis of the National Malaria Eradication Program. As a corollary benefit, there was a sharp decline in the incidence of VL due to the reduced prevalence of the vector to extremely low levels, resulting in substantial decreases in the number of KA cases. In the early 1970s, a surge in the number of cases was noted, and since then, it has taken the shape of the current epidemic. In 1990-91, the National Kala-azar Control Program was launched in India, though without much impact due to the diminishing efficacy of treatment with pentavalent antimonial. This was followed by the introduction of highly effective amphotericin B deoxycholate. In 2005, the Kala-azar Elimination Program (KAEP) was launched jointly by India, Bangladesh, and Nepal, with treatment initially with oral miltefosine, succeeded later by single-dose liposomal amphotericin B (AmBisome), and in 2023, India achieved the goal of kala-azar elimination, defined as an incidence below 1 per 10,000 at sub-district (block) level. Patients with post kala-azar dermal leishmaniasis, HIV-VL coinfection, and undiagnosed/untreated VL patients are the human sources for the vector. They may herald an outbreak resulting in the commencement of a new epidemic. Active case detection, early diagnosis, and prompt, complete treatment are required to prevent fresh transmission. Periodic updates of health personnel, community awareness, and continued availability of the theragnostics are important steps for early detection and containment of an outbreak.